Feasibility Study of a Newly Developed Hybrid Energy Device Used During Laparoscopic Liver Resection in a Porcine Model. (June 2019) - Wakabayashi, Taiga; Abe, Yuta; Kanazawa, Akishige; Oshima, Go; Kodai, Shintaro; Ehara, Kazuhisa; Kinugasa, Yusuke; Kinoshita, Takahiro; Nomura, Akinari; Kawakubo, Hirofumi; Kitagawa, Yuko
Background . Although various devices have been clinically used for laparoscopic liver resection (LLR), the best device for liver parenchymal transection remains unknown. Olympus Corp (Tokyo, Japan) developed a laparoscopic hybrid pencil (LHP) device, which is the first electric knife to combine ultrasound and electric energy with a monopolar output. We aimed to evaluate the feasibility of using the LHP device and to compare it with the laparoscopic monopolar pencil (LMP) and laparoscopic ultrasonic shears (LUS) devices for LLR in a porcine model. Methods . Nine male piglets underwent laparoscopic liver lobe transections using each device. The operative parameters were evaluated in the 3 groups (n = 24 lobes) during the acute study period. The imaging findings from contrast-enhanced computed tomography and histopathological findings of autopsy on postoperative day 7 were compared among groups (n = 6 piglets) during the long-term study. Results . The transection time was shorter ( P = .001); there was less blood loss ( P = .018); and tip cleaning ( P < .001) and instrument changes were less often required ( P < .001) in the LHP group than in the LMP group. The LHP group had fewer instances of bleeding ( P < .001) and coagulator usage ( P < .001) than did the LUS group. In the long-term study, no postoperative adverse events occurred in the 3 groups. The thermal spread and depth of the LHP device were equivalent to those of the LMP and LUS devices (vs LMP: P = .226 and .159; vs LUS: P = 1.000 and .574). Conclusions . The LHP device may be an efficient device for LLR if it can be applied to human surgery.